2021
DOI: 10.1016/j.envres.2021.110977
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature, and of relative and absolute humidity on COVID-19 incidence in England - A multi-city time-series study

Abstract: Background SARS-CoV-2 caused the COVID-19 pandemic in 2020. The virus is likely to show seasonal dynamics in European climates as this is often the case for respiratory viruses and for coronaviruses. Analysing the association with meteorological factors will be helpful to anticipate how cases will develop with changing seasons. Methods Routinely measured ambient daily mean temperature, absolute humidity, and relative humidity were the explanatory variables. Test-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 45 publications
5
69
1
Order By: Relevance
“…Paradoxically, increased epidemic intensity in wave 2 first emerged in states in southern latitudes and with low altitudes, in the hottest states in the hottest time of the year. Studies identified the range of 5-15°C as a significant temperature zone for high incidence of COVID-19 cases (14)(15)(16). Outside this temperature range, COVID-19's temperature response becomes unclear (14,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, increased epidemic intensity in wave 2 first emerged in states in southern latitudes and with low altitudes, in the hottest states in the hottest time of the year. Studies identified the range of 5-15°C as a significant temperature zone for high incidence of COVID-19 cases (14)(15)(16). Outside this temperature range, COVID-19's temperature response becomes unclear (14,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In the second stage, coefficients and covariance matrices from the first stage models were pooled using meta-analysis. This approach controls for city-level confounders, relaxes the strong assumption that the exposure-1 lag response is not city-specific and has been deployed in a recent similar study (Nottmeyer and Sera 2021).…”
Section: Methodsmentioning
confidence: 99%
“…, denotes a crossbasis for temperature on day t considering lag l, constructed using natural splines with 3 prespecified degrees of freedom for both the exposure and lag bases (Nottmeyer and Sera 2021 found that larger values for the degrees of freedom incurred a loss of precision for the estimates) with 1 the corresponding vector of coefficients. We considered lag range 0 through 10 days inclusive as in recent studies (Lauer et al, 2020;Nottmeyer and Sera 2021). dow denotes the day of week fitted as dummy variables, with the corresponding vector of coefficients.…”
Section: First Stage Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A few researchers have already exhorted about signi cant association of environmental parameters to COVID-19 transmission (Azuma et al, 2020;Bherwani et al, 2020;Eslami and Jalili, 2020;Gupta and Pradhan, 2020a;Kifer et al, 2021;Rume and Islam, 2020;Saadat et al, 2020;Shakil et al, 2020). There are also a few global as well as regional studies that had been carried out in the context of China, USA, England, Germany, Spain, Italy, Indonesia, Iran, Pakistan, Bangladesh, India, and found signi cant correlation between weather parameters and the COVID-19 cases (Ahmadi et al, 2020;Fadli et al, 2020;Ficetola and Rubolini, 2021;Gupta and Pradhan, 2020b;Liu et al, 2020b;Ma et al, 2020;Mehmood et al, 2021;Nottmeyer and Sera, 2021;Qi et al, 2020;Tosepu et al, 2020). Studies carried out by Bochenek et al, 2021;Borah et al, 2020;Briz-Redón and Serrano-Aroca, 2020;Emediegwu, 2021;Guo et al, 2021;Mecenas et al, 2020;Runkle et al, 2020;Şahin, 2020;Sil and Kumar, 2020 suggested that warm and humid condition days incubation period, lower the number of cases (Şahin, 2020).…”
Section: Introductionmentioning
confidence: 99%